Preoperative prone position exercises: a simple and novel method to improve tolerance to kyphoplasty for treatment of single level osteoporotic vertebral compression fractures - Guangzhou Li; Hao Liu; Qing Wang; Dejun Zhong (BMC Musculoskeletal Disorders, 2017)
Abstract Background The proper choice of anesthesia for kyphoplasty remains controversy. There are only a few clinical studies specially focusing on and giving detailed information about this treatment under local anesthesia with or without conscious sedation. To evaluate the effect of preoperative prone position exercises on patient tolerance to percutaneous kyphoplasty under local anesthesia. Methods Eighty-three patients with single level osteoporotic vertebral compression fractures were nonrandomly assigned to undergo percutaneous kyphoplasty under local anesthesia with preoperative prone position exercises or without. The number of procedure with or without a pause, need for intravenous sedation, and patient satisfactory were recorded and analyzed. Clinical outcomes were assessed using the visual analog scale and the Oswestry Disability Index. The follow-up time was 6 months. Results The baseline characteristics of both groups were comparable. The number of procedure without a pause in the exercises group was more than the control group (30/42 patients and 10/41 patients, respectively, P < 0.001), and fewer patients required intravenous sedation in the exercises group (7/42 and 28/41, respectively, P < 0.001). Patients in the exercises group were more satisfied compared to the control group (41/42 and 32/41, respectively, P < 0.01). There were no significant differences between the two groups with regard to improvement in pain and functional scores at all postoperative intervals. Conclusions Prone position exercises may improve patient tolerance and satisfaction and reduce the need for intravenous sedation for those with single level vertebral compression fracture undergoing kyphoplasty under local anesthesia. We expect large sample size and multi-center randomized controlled trial studies to be conducted.